A case of pica in childhood with intellectual disability: focus on non-psychopharmacology management (Medical Journal of Indonesia, 2020)
Non-psychopharmacology management is crucial in pica in childhood with intellectual disability. This case report shows the effectiveness of pica management centered on behavioral therapy over the use of pharmacotherapy in improving the patient’s symptoms. A-7-year-old girl had been eating plastic bags since she was 3. In the last 6 months, this behavior worsened and coupled with emotional and behavioral problems. Her intellectual function showed that she had a moderate intellectual disability, which was confirmed by her intelligence quotient test result. She also had iron deficiency anemia and constipation. Non-psychopharmacological management was delivered to the patient and family. The patient was treated with a reinforcement strategy of behavioral therapy, involving parental education during the process to stimulate desirable behavior, discourage unwanted behavior, and improve parent-child interaction. After six sessions of behavioral therapy and parental psychoeducation, the patient showed improvement as the frequency of eating nonfood substances was decreasing.